John G. Foster papers - Foster, John G. (John Gray), 1823-1874.
Letterbook for the Dept. of Florida.
Army officer.
Collection material in English.
Keywords: United States. -- Army. -- Department of Florida; United States -- History -- Civil War, 1861-1865.; Army officers